Analisis Perbandingan Metode Pd T-05-2005-B Dan Pedoman No. 002/M/Bm/2013 Dalam Perencanaan Overlay Pada Jalan Garuda Sakti Pekanbaru - Jauhari, Agit; Yusa, Muhammad; Elianora, Elianora (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The road is a land transportation infrastructure that has an important role to facilitate economic activity in a certain place. Garuda Sakti street Tampan district is a causeway that connects city of Pekanbaru to Patapahan Kampar, and also be a connecting road from Pekanbaru to Ujung Batung Rokan regency, damage found on the road can cause inconvenience to road users. So as to improve the comfort and safety of road users do maintenance by calculating the added thick layer ( overlay ) on roads Garuda Sakti Km 001+000 until 004+000 by comparing the two different methods, namely methods pd T-05- 2005-B and User Guidelines Pavement Design number 002/M/BM/2013, resulting in different thickness that is equal to 24 cm with D wakil 1616 mm and FK 19,36% for method pd T-05-2005-B and 14 cm with Dwakil and FK 20% fot guidelines Number 002/M/BM/2013, with the type of handling that is reconstruction. Keywords :added thick layer , Pd Method T-05-2005-B, guidelines Number .002 / M / BM / 2013